2014
DOI: 10.2485/jhtb.23.63
|View full text |Cite
|
Sign up to set email alerts
|

Cell Differentiation on Nanoscale Features of a Titanium Surface: Effects of Deposition Time in NaOH Solution

Abstract: The present study aimed to investigate cellular behavior on nanoscale features of a titanium surface by controlling the deposition time in NaOH. These effects were then evaluated for osteogenic differentiation of rat bone marrow cells to potentially increase the success rate of titanium implants. Titanium disks were left untreated or soaked in 10 M NaOH for 5 min, and 1h, 3h, 9h and 24 h. Scanning electron and probe microscopy were used to evaluate the nanoscale features. Rat bone marrow cells were seeded on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 28 publications
4
25
0
Order By: Relevance
“…The contact angles of the alkali-treated titanium alloy disks gradually decreased compared with those of the control group, which suggests that the wettability of the surface of the test group was decreased by NaOH treatment. Xing and Fujino and colleagues showed that a surface roughness between 13 and 16 nm was optimal for RBM cell culture [23,24]. The nanonetwork structure formed on the titanium alloy disks here is similar to the hierarchical structure reported by Zhao and coworkers [25].…”
Section: Discussionsupporting
confidence: 83%
“…The contact angles of the alkali-treated titanium alloy disks gradually decreased compared with those of the control group, which suggests that the wettability of the surface of the test group was decreased by NaOH treatment. Xing and Fujino and colleagues showed that a surface roughness between 13 and 16 nm was optimal for RBM cell culture [23,24]. The nanonetwork structure formed on the titanium alloy disks here is similar to the hierarchical structure reported by Zhao and coworkers [25].…”
Section: Discussionsupporting
confidence: 83%
“…e contact angles of the alkali-treated titanium disks gradually decreased in comparison with those of the control group, indicating that the wettability of the surface of the test group was reduced by NaOH treatment. In previous studies, a surface roughness of between 13 and 16 nm was found to be optimal for RBM cell culture [18,19]. e nanonetwork structure framed on the titanium disks here was like the hierarchical structure outlined by Zhao et al [12].…”
Section: Discussionsupporting
confidence: 58%
“…Surfaces with nanostructures are well-known to possess increased surface area compared with those without such features 5,6,16) .…”
Section: Discussionmentioning
confidence: 99%